2016
DOI: 10.1177/0956462416641816
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse HIV-associated seborrheic dermatitis – a case series

Abstract: Seborrheic dermatitis (SD) is reported to have distinct clinical and histologic presentations in patients with HIV infection. Here we present 20 cases to further define some of these unique characteristics. Common features include erythematous, scaly papules, and plaques involving areas beyond the typical seborrheic distribution; thick, greasy scale on the scalp; and an increased frequency of erythroderma. Histologically, there is widespread parakeratosis, spongiosis, and necrotic keratinocytes. Treatment is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
(26 reference statements)
0
24
2
2
Order By: Relevance
“…Several studies have challenged the role of Malassezia in SD in HIV‐infected patients. One study done in HIV‐positive patients showed either negative or limited growth of Malassezia . On the other hand, a significantly higher number of Malassezia was cultured from HIV‐negative patients with SD.…”
Section: A Complex Relationship With Systemic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have challenged the role of Malassezia in SD in HIV‐infected patients. One study done in HIV‐positive patients showed either negative or limited growth of Malassezia . On the other hand, a significantly higher number of Malassezia was cultured from HIV‐negative patients with SD.…”
Section: A Complex Relationship With Systemic Diseasesmentioning
confidence: 99%
“…These studies suggest that HIV‐positive patients may have a different pathogenic mechanism than SD in individuals with an intact immune system. These patients are also often refractory to standard SD treatments, requiring prolonged courses of topicals and systemic antifungals, and treatment failure is common …”
Section: A Complex Relationship With Systemic Diseasesmentioning
confidence: 99%
“…Humoral and cellular immunity have been studied in patients with SD, though with conflicting results. 5,6 Nonetheless, an alteration of immune responses has been described: NKs increase, low IgG titers, IL-2 and INFγ reduction. 6 Plasmatic polyunsaturated fatty acid (PUFA) deficits, sebaceous squalene and waxes reduction have often been found in patients with the copresence of HIV and SD.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nonetheless, an alteration of immune responses has been described: NKs increase, low IgG titers, IL-2 and INFγ reduction. 6 Plasmatic polyunsaturated fatty acid (PUFA) deficits, sebaceous squalene and waxes reduction have often been found in patients with the copresence of HIV and SD. The plasma deficit of PL-PUFA is closely associated with reduced blood levels of vitamin E, glutathione peroxidase and ubiquinone, 7 suggesting a possible role of oxidative stress in SD development.…”
Section: Introductionmentioning
confidence: 99%
“…While established associations such as human immunodeficiency virus (HIV) and parkinsonism are important and point towards aetiological hypotheses for the disease, other associations have been described and investigated only in either small samples or in specialized, nongeneralizable populations. The present study utilizes data from the Rotterdam Study, a large prospective cohort study.…”
mentioning
confidence: 99%